Shoulder instability in the tennis player: open surgical treatment - Rodosky, M. W. (1999)
Shoulder instability in the tennis player may be the result of macrotrauma or microtrauma. Common symptoms are anterior shoulder pain, instability symptoms with the dead arm syndrome, and a subjective feeling of subluxation. General physical findings are an increased translation and range of motion in comparison to the contralateral side, and positive impingement and apprehension tests. Injection studies and/or an MRI arthrogram may be performed to confirm the diagnosis. After more than 6 months of failed conservative therapy, operative treatment may be considered. In case of micro-instability or hyperlaxity with secondary functional impingement, a bursectomy and decompression may suffice. An open or arthroscopic stabilisation procedure should be used in cases of more severe instability or failure of the above. The advantages of open stabilisation procedures are the longer rack record, the lower recurrence rates and the increased power to tighten and overlap he capsule in anatomic fashion. The disadvantages, however, are the morbidity with respect to the rotator cuff and more difficulties in returning to the same level of sport. The open stabilisation technique used by the author is the anatomic capsular approach. The cuff may be taken down or be split. Splitting has the advantage of an improved return to overhead sports. The advantage of a cuff takedown is that it enables a humeral capsular split (with more power to the capsule shift) instead of a glenoid based capsular split. Post-operative rehabilitation consists of a sling at night for four weeks and a daytime sling for two weeks. Assisted active range-of-motion exercises are initiated immediately, with gradual external rotation and scaption. The goal is to reach functional range of motion at 8-10 weeks post-operatively.